Study on health status of farmed shing (Heteropneustes fossilis) in Mymensingh region - Uddin, Md Asek; Islam, Md Ariful; Islam, Rashedul; Yesmin, Rabeya; Halim, KM Abdul; Hasanuzzaman, KM (Research in Agriculture Livestock and Fisheries, 2020)
Health status investigation of shing (Heteropneustes fossilis) was carried out through clinical and histopathological observations. During four months from January 2018 to April 2018. The data were collected from eight fish farms. Clinical signs of fish were physical deformity, reddish whitish lesions, abrasion and reduced mucus in the months of January and February from the investigated fish farms. Clinically fish were almost normal in the months of March and April. Histopathlogically observed pathological changes in gill were lamellar missing, splitted gill lamellae, hemorrhage, hypertrophy, vaccums and presence of parasites in January and February. In case of liver the examined fish had hemorrhage, vaccums, necrosis and fat bodies also in the months of January and February. Organs of the examined fishes were almost normal in the months of March and April. The purpose of the study was to determine the health status of farmed shing. The main objectives of the study were to observe clinical and histopathological changes in liver and gill of farmed shing (H. fossilis) at various fish farms of Mymensingh region and to determine the health status of the shing in the investigated months. From the present study, it was found that external organs like gill were more affected compared to internal organ like liver. From the present investigation, it was also observed that the fish were more affected in the months of January and February i.e. in winter season. Res. Agric., Livest. Fish.6(3): 445-455, December 2019